Transcriptome analysis of soybean roots in response to boron deficiency - Jiahua Guo; Xiaoyu Zhao; Xuejiao Wang; Limin Jia; Yu Zhou; Min Xie; Qiang Li; Erhu Su; Li Fan (Biotechnology & Biotechnological Equipment)
Boron (B) deficiency is detrimental to Glycine max (L.) Merr., which is one of the leading oil crops. In this study, physiological analysis of soybean seedlings under B deficiency and control after 12 h, 24 h, 72 h and 8 days was carried out, and the roots were subjected to transcriptome sequencing analysis. The results showed that under B deficiency, the plant height, SPAD and chlorophyll fluorescence value of soybean seedlings decreased significantly, indicating that B stress significantly inhibited plant growth and photosynthesis. RNA-seq revealed a total of 5126 DEGs (Differentially Expressed Genes), and nine DEGs co-existed at the four-time points, among which GLYMA_03G130600 regulates transcription factor ORG3, which is related to plant growth. GO analysis revealed a total of annotated 4018 DEGs, among which the terms plasma membrane, extracellular, enzyme activity, ion transport metabolic process and oxidoreductase activity were significantly enriched at the four time points, which might hinder the growth of soybean and accelerate senescence. KEGG analysis showed that at level 1, the DEGs were mainly enriched in photosynthesis-related, phenylpropanoid biosynthesis, nitrogen metabolism and plant hormone signal transduction. At level 2 of secondary metabolism, the DEGs were mainly enriched in energy metabolism and amino acid metabolism pathways, which indicates that B stresses mainly affect photosynthesis, hormone regulation and amino acid metabolism of soybean, thus affecting plant growth. The above results give deeper insight into the soybean response to B deficiency and lay the foundation for further studies of the molecular mechanism of soybean response to boron deficiency.